Awareness and knowledge of myopia complications and control among myopic subjects in Saudi Arabia - Moafa, Majid A.; Alrasheed, Saif Hassan; Almutairi, Rakan Massad; Alluwimi, Muhammed S.; Alghamdi, Waleed M.; Elmadina, Abdelaziz Mohamed; Mutwali, Raghda F. (International ophthalmology, 2025)
Purpose There is a reported global increase in myopia, including in Saudi Arabia, where it has become a public health issue. This study aims to assess the awareness and knowledge of myopia complications and control among myopic individuals. Methods A cross-sectional study of 463 myopic subjects was conducted in Saudi Arabia between May and October 2023. Data were collected through a self-administered questionnaire. Descriptive analyses were performed, and P < 0.05 was used to determine statistical significance. Results Most participants (403; 87.04%) received information about myopia from eye care professionals, followed by social media (29; 6.26%). Only 39.1% understood the vision problems and complications related to myopia. The common methods of myopia correction were eyeglasses (70.8%), contact lenses (7.6%), and refractive surgery (6.3%). Over half (51.6%) recognized that myopia is a sign of an ocular disorder, while 38.0% did not realize myopia could lead to other ocular complications. Many (60.3%) reported that systemic disorders like diabetes and hypertension influence myopia development. About 23.3% believed myopia does not lead to blindness. Nearly 47.3% agreed myopia development can be controlled, while 16% did not. Participants identified environmental (54.2%), genetic (20.3%), and wearing eyeglasses (5.8%) as contributing factors to myopia development. A multinomial logistic regression revealed that gender was a significant predictor, with males being less likely than females to adopt myopia control measures (β = –0.66, P = 0.016). Age was a significant positive predictor, with older individuals more likely to be aware of myopia-related complications (β = 0.0243, P = 0.015). Conclusion There is a lack of awareness regarding the complications, appropriate management strategies, and vision loss associated with myopia. Eye care professionals should organize public awareness programs to enhance community knowledge and practices on myopia control.